Stone cold : a Jesse Stone novel - Parker, Robert B., 1932-2010 (No Exit Press, 2004)
Paradise, Massachusetts.Police chief Jesse Stone returns, tracking the path of a pair of thrill killers ... Jesse Stone has a problem no officer of the law likes to face: dead bodies keep appearing, but clues do not.A man takes his dog out for a run on the beach, only to be discovered hours later - with two holes in his chest.A woman drives her Volvo to the store to do some grocery shopping, and is then found dead, her body crumpled behind her loaded shopping cart. A commuter takes a shortcut home from the train, and never makes it back to his house. Hunting down a serial killer is difficult and dangerous in any town, but in a town like Paradise, where the selectmen and the media add untold pressures, Jesse feels considerable heat.Already walking an emotional tightrope, he stumbles; he's spending too much time with the bottle, and with his ex-wife - neither of which helps him, or the case.And the harder these outside forces push against him, the more Jesse retreats into himself, convinced - despite all the odds - that it's up to him alone to stop the killing. 'As good as a top-drawer Spenser' - Publishers Weekly 'Very readable, slick and professional' - The Standard 'Nobody does it better than Parker...' - The Sunday Times